2017
DOI: 10.5217/ir.2017.15.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of computed tomographic features in differentiating intestinal tuberculosis from Crohn's disease: a systematic review with meta-analysis

Abstract: Abdominal computed tomography (CT) can noninvasively image the entire gastrointestinal tract and assess extraintestinal features that are important in differentiating Crohn's disease (CD) and intestinal tuberculosis (ITB). The present meta-analysis pooled the results of all studies on the role of CT abdomen in differentiating between CD and ITB. We searched PubMed and Embase for all publications in English that analyzed the features differentiating between CD and ITB on abdominal CT. The features included comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 37 publications
3
25
0
1
Order By: Relevance
“…Our data showed that C-type and D-type were mainly in the nonactive, whereas A-type and B-type were in the active. These results are consistent with the results reported in some studies [ 4 , 14 ]. During the active phase, the mucosal layer of the lesion is enhanced significantly as a result of the inflammatory reaction.…”
Section: Discussionsupporting
confidence: 94%
“…Our data showed that C-type and D-type were mainly in the nonactive, whereas A-type and B-type were in the active. These results are consistent with the results reported in some studies [ 4 , 14 ]. During the active phase, the mucosal layer of the lesion is enhanced significantly as a result of the inflammatory reaction.…”
Section: Discussionsupporting
confidence: 94%
“…Unlike the previous attempts by us and others, this study has given two features, which are almost exclusive to either disease, lymph nodes with necrosis for ITB, or a combination of long segment involvement and VF/SC ratio > 0.63 for CD. Necrotic lymph nodes in ITB is a known fact as highlighted by previous studies and in a meta‐analysis published by our group recently, and the present study has re‐confirmed this finding. For diagnosing CD, the ECCO guidelines have suggested a combination of clinical, endoscopic, and histological features.…”
Section: Discussionmentioning
confidence: 99%
“…In a significant number of cases (44.5%), granulomas were seen in a submucosal location, and the predominant type of inflammation seen in the lamina propria was lymphoplasmacytic [ 1 ]. Antimicrobial therapy (RIPE: rifampicin, isoniazid, pyrazinamide, and ethambutol for two months followed by rifampicin plus isoniazid for an additional six months) remains the mainstay of the treatment for GI TB; however, surgical or endoscopic intervention is often required in cases complicated by perforation or obstruction [ 10 ]. In one study, colonoscopic follow-up after 2-3 months of anti-TB therapy showed complete healing of the ulcers and erosions [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%